-19th+12=-14th-8

Simple and best practice solution for -19th+12=-14th-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -19th+12=-14th-8 equation:


Simplifying
-19th + 12 = -14th + -8

Reorder the terms:
12 + -19ht = -14th + -8

Reorder the terms:
12 + -19ht = -8 + -14ht

Solving
12 + -19ht = -8 + -14ht

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '14ht' to each side of the equation.
12 + -19ht + 14ht = -8 + -14ht + 14ht

Combine like terms: -19ht + 14ht = -5ht
12 + -5ht = -8 + -14ht + 14ht

Combine like terms: -14ht + 14ht = 0
12 + -5ht = -8 + 0
12 + -5ht = -8

Add '-12' to each side of the equation.
12 + -12 + -5ht = -8 + -12

Combine like terms: 12 + -12 = 0
0 + -5ht = -8 + -12
-5ht = -8 + -12

Combine like terms: -8 + -12 = -20
-5ht = -20

Divide each side by '-5t'.
h = 4t-1

Simplifying
h = 4t-1

See similar equations:

| -5x-7(-2x+3)=-66 | | 3+2.7x=4.7 | | 3(2x-5)=5(x-4)1x+5 | | 3z=-7+17 | | 8k-4.7=3k+0.4 | | 28=-48 | | F(x)=2w^2-5w-14 | | 3x(5x-5)= | | 1.5(5-x)=.25 | | -2.3q+16=-50-38 | | v=x(24-2x)(16-2x) | | (2x+8)=(3x-4) | | 9t+5=104 | | 1.5(5-x)=.75 | | -3y=15+15x | | X^3+x^2+x+4=0 | | 4a+2b=40 | | 12y+26=90 | | 8x=y-4 | | 4.05+14.4=5.5(p+3) | | -2y=12x+5 | | -2.3q+16=50-38 | | -5x-6(6x-6)=-292 | | -6p=-3clear | | 3x+2y=-4solvey | | 18-4(2x+5)=12-6 | | 14x-7x=63 | | Xy-3x=y | | 10y=50-8x | | 4.05+14.50=5.50(p+3) | | 7x+2(-7x+21)=0 | | 5*m=13 |

Equations solver categories